The Socio-Economic Impacts of the Smallholder Cotton Intensification Program on Farmers in Grobogan Regency during the New Order Government - Ramadhan, Fauzan Syahru; Khairana Zata Nugroho; Desi Susanti; Utomo, Ilham Nur (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This article examines the impact of the Smallholder Cotton Intensification Program on the socio-economic lives of farmers in the Grobogan Regency during the New Order era. The background for implementing the Smallholder Cotton Intensification Program in Grobogan Regency was because the area was rainfed land and moor or dry rice fields, so it was very promising for the development of cotton in the area. The method used in compiling this article is the historical method which consists of four stages, namely heuristics, criticism, interpretation and historiography. Through this research, the fact was obtained that the implementation of the Smallholder Cotton Intensification Program in Grobogan Regency could be said to be successful because it was supported by several factors such as the type of land suitable for planting cotton, the planting area that was still available, the response of farmers who were willing to accept the presence of the program because they had felt the good results so that it was considered a commodity that could increase their income, as well as good coordination between the Grobogan Regency Plantation Service and the Plantations Limited Company of Indonesia (PT. Perkebunan, PTP) XVIII as the management in successing the implementation of the program. Thus, it can be concluded that the successful implementation of the Smallholder Cotton Intensification Program had influenced the socio-economic life of farmers in Grobogan Regency, such as the establishment of farmer groups, wider employment opportunities, and increasing amount of farmer incomes as well.